The Combined Effect of Photobiomodulation and Curcumin on Acute Skin Wound Healing in Rats - Amini, Abdollah; Soleimani, Hasan; Rezaei, Fatemehalsadat; Ghoreishi, Seyed Kamran; Chien, Sufan; Bayat, Mohammad (Journal of Lasers in Medical Sciences, 2021)
Introduction: Abnormal wound repair is a cause for a considerable expense, as well as patient morbidity and mortality. Here, we investigated the combined impact of photobiomodulation (PBM) and curcumin on a rat experimental model of an acute skin wound. Methods: A round full-thickness wound was created on the back of each rat. We divided the rats into the following four groups. Group one was the control group. Group two received pulse wave (PW) PBM at a dose of 890 nm, 80 Hz, and 0.2 J/cm2. Group 3 received 40 mg/kg curcumin by gastric gavage and group 4 was treated with PWPBM + curcumin. We measured the wound area on days 4, 7, and 15, and performed microbiologically and tensiometry examinations. Results: There was markedly improved wound contraction in the curcumin (7.5 ± 0.57; P=0.000), PBM (8.5 ± 1.2; P=0.000), and PBM + curcumin (14.5 ± 4.3; P=0.002) groups relative to the control group (25 ± 6). PBM (100 ± 7.3; P=0.005), and PBM + curcumin (98 ± 6; P=0.005) groups meaningfully improved tensile strength relative to the control group (61 ± 8.2). On day 15, the PBM (10 ± 5; P=0.000), curcumin (14 ± 4.5, P=0.000), and PBM + curcumin (27.3 ± 8.3; P=0.000) groups meaningfully decreased microbial flora relative to the control group (95 ± 6). Conclusion: We concluded that the PBM and PBM + curcumin groups meaningfully accelerated wound healing of the acute skin wound in the rats. The results of the PBM group were statistically more effective than the curcumin alone and PBM + curcumin-treated groups. DOI:10.34172/jlms.2021.09